Nanocrystalline diamond sheets as protective coatings for fiber-optic measurement head. (January 2020) - Kosowska, Monika; Majchrowicz, Daria; Ficek, Mateusz; Wierzba, Paweł; Fleger, Yafit; Fixler, Dror; Szczerska, Małgorzata
Abstract: Fiber-optic sensors find numerous applications in science and industry, but their full potential is limited because of the risk of damaging the measurement head, in particular, due to the vulnerability of unprotected tips of the fiber to mechanical damage and aggressive chemical agents. In this paper, we report the first use of a new nanocrystalline diamond structure in a fiber-optic measurement head as a protective coating of the fiber tip. The nanocrystalline sheet structures, produced with the use of Microwave Plasma Assisted Chemical Vapor Deposition System (MW PA CVD), were characterized by Scanning Electron Microscopy (SEM) and successfully transferred from the deposition substrate onto the surface of the tip of a single-mode fiber sensor head. A Fabry-Perot sensing interferometer for distance measurement comprising that fiber was built. The measurement results were compared with numerical modeling. High values of achieved correlation coefficients (R2 > 0.99) between a linear model and distance measurements data indicate that the diamond sheet does not affect the correct operation of the sensor while extending its potential scope of applications. Graphical abstract: Image 10802